Long Non-coding RNA Signatures Associated With Liver Aging in Senescence-Accelerated Mouse Prone 8 Model - Zhang, Shuai; Duan, Juanjuan; Du, Yu; Xie, Jinlu; Zhang, Haijing; Li, Changyu; Zhang, Wensheng (Frontiers in Cell and Developmental Biology, 2021)
The liver is sensitive to aging because the risk of hepatopathy, including fatty liver, hepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma, increases dramatically with age. Long noncoding RNAs (lncRNAs) are >200 nucleotides long and affect many pathological and physiological processes. A potential link was recently discovered between lncRNAs and liver aging; however, comprehensive and systematic research on this topic is still limited. In this study, the mouse liver genome-wide lncRNA profiles of 8-month-old SAMP8 and SAMR1 models were explored through deep RNA sequencing. A total of 605,801,688 clean reads were generated. Among the 2,182 identified lncRNAs, 28 were differentially expressed between SAMP8 and SAMR1 mice. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) surveys showed that these substantially dysregulated lncRNAs participated in liver aging from different aspects, such as lipid catabolic (GO:0016042) and metabolic pathways. Further assessment was conducted on lncRNAs that are most likely to be involved in liver aging and related diseases, such as LNC_000027, LNC_000204E, NSMUST00000144661.1, and ENSMUST00000181906.1 acted on Ces1g. This study provided the first comprehensive dissection of lncRNA landscape in SAMP8 mouse liver. These lncRNAs could be exploited as potential targets for the molecular-based diagnosis and therapy of age-related liver diseases.